2012
DOI: 10.1212/wnl.0b013e31824c46be
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline as a rescue treatment for DMD

Abstract: Objective: To determine whether pentoxifylline (PTX) slows the decline of muscle strength and function in ambulatory boys with Duchenne muscular dystrophy (DMD). Methods:This was a multicenter, randomized, double-blinded, controlled trial comparing 12 months of daily treatment with PTX or placebo in corticosteroid-treated boys with DMD using a slow-release PTX formulation (ϳ20 mg/kg/day). The primary outcome was the change in mean total quantitative muscle testing (QMT) score. Secondary outcomes included chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 35 publications
1
27
0
2
Order By: Relevance
“…Thus, its efficacy in these subjects could not be assessed, and alternative routes of administration have been investigated. In a 12-month double-blind study of 64 DMD boys, treatment with a slow-release pentoxifylline formulation was better tolerated, but did not improve or halt the deterioration of muscle strength and function 200 .…”
Section: Phoshodiesterase Inhibitionmentioning
confidence: 94%
“…Thus, its efficacy in these subjects could not be assessed, and alternative routes of administration have been investigated. In a 12-month double-blind study of 64 DMD boys, treatment with a slow-release pentoxifylline formulation was better tolerated, but did not improve or halt the deterioration of muscle strength and function 200 .…”
Section: Phoshodiesterase Inhibitionmentioning
confidence: 94%
“…This agent does not appear to exert anti-fibrotic effects through modulation of TGF-β, but instead is thought to counteract nitric oxide synthase deficiency at the myofiber membrane and improve blood flow. Pentoxifylline, a nonselective phosphodiesterase inhibitor with both anti-inflammatory and antifibrotic activities (thought to act through modulation of TGF-β signaling) (106), nonetheless failed to prevent deterioration in muscle function over a 1-year evaluation period in DMD patients (Table 1) (107). Pirfenidone, an antifibrotic agent (108) that has been shown to inhibit the secretion of TNF-α and TGF-β and to inhibit TGF-β signaling by preventing nuclear accumulation of active Smad2/3 complexes in animal studies (109), is approved in Europe and the United States for idiopathic pulmonary fibrosis (Table 1).…”
Section: Drugs With Anti-fibrotic Activitymentioning
confidence: 99%
“…Despite the results, the investigators point out that the PTX treatment group showed a trend toward slower rate of decline and raise the possibility that a longer study may identify a beneficial, synergistic role for PTX. They also emphasize that future studies need to evaluate higher doses of PTX since doses of 120 mg/kg were necessary to attenuate the upregulation of TGF beta pathways in nonhuman primates and the negative results in the current study evaluated a dose of 20 mg/kg [56].…”
Section: Phosphodiesterase Inhibitorsmentioning
confidence: 89%
“…Pentoxifylline (PTX) is a phosphodiesterase inhibitor that has recently undergone Phase II clinical trial assessment [56]. In preclinical studies, PTX treatment slowed muscle strength deterioration by 51% in exercised mdx mice [57].…”
Section: Phosphodiesterase Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation